Labour Absorption in the Manufacturing Industry Sector in Central Java Province Indonesia - Haedzar P, Rizqi; Sri Yani Kusumastuti; Erista Nurfianingrum; Syafri (Asean International Journal of Business, 2022)
The purpose of this research is to measure the effect of Industrial Investment, GRDP of Central Java Regency/City, Production Value, Number of Companies, and Regency/City Minimum Wage on Manpower Absorption in Manufacturing Industry in Central Java Province. Methodology      :              The study used the Ordinary Least Square (OLS) Multiple Regression Method. The data used is cross-sectional data for each indicator in all districts and cities in Central Java Province in 2018. Results  :              The results of the study concluded that Industrial Investment, Production Value and Number of Companies were positively and significantly related to the employment of the manufacturing industry in Central Java Province. District/City GRDP and MSEs show results that are contrary to the theory and are not significant.